Analisis Realisasi Alokasi Dana Desa (ADD) di Kabupaten Pulau Morotai - Jamiludin Hasan; Yuliana Yuliana (Peneliti.net, 2021)
This study aims to determine the Efficiency and Effectiveness of Village Fund Allocation in Pangeo Village in 2016-2020. The results of the Efficiency ratio analysis show that in Pangeo Village it is very efficient in managing the Village Fund. in terms of the management aspect of the ineffective Village Fund Allocation in Pangeo Village, Morotai Jaya District, Morotai Island Regency Government can be seen as follows: 1) Pangeo Village is very efficient in managing its ADD, this can be seen from the results of the calculation of the efficiency ratio of 1% in 2016, 1.00% in 2017, 1% in 2018, 1% in 2019 and 1% in 2020. 2) Financial performance (effectiveness) in Pangeo Village for 2016 to 2020 in terms of management aspects Allocations Ineffective Village Funds can be seen from the percentage starting from 2016 of 8.62%, in 2017 of 7.70%, in 2018 of 7.5%, in 2019 of ar 7% and in 2020 by 6.04%.